(untitled) (Modern education and development, 2025)
This article explores the pedagogical possibilities of shaping spiritual education among youth through the integration of national values. It analyzes how cultural heritage, moral traditions, and national identity can serve as foundational elements in fostering ethical behavior, civic responsibility, and emotional maturity in students. The study highlights effective teaching methods, curriculum integration, and community-based initiatives that contribute to the development of a spiritually enriched generation. By emphasizing the role of national values in the education system, the article underlines the importance of nurturing both intellectual and moral development in young people.